Institutional Environment Tools for Small and Medium-Sized Enterprises Development - Verbivska, Liudmyla; Maslov, Anatoly; Potryvaieva, Natalia; Berezhnytska, Uliana; Koliadych, Oleksandr (My University, 2021)
This work's relevance is due to the need to improve the use of tools to stimulate the development of enterprises and the development of effective measures of government influence on the market economy. The article discusses the institutional environment's main characteristics in which enterprises of the real sector of the economy operate. Arguments showing the need for state support and development of small business, from the point of view of a key factor in the development of both the national economy and the factor of stabilization of the social sphere, are presented. The characteristic is given, and the main nuances of the impact and transformation of the institutional environment with the help of available tools are considered to achieve the effect of stable and long-term development of small and medium-sized enterprises. The article attempts to highlight the existing problems and the complex nature of the impact of instruments on enterprises' institutional environment.
Keywords: institutions, institutional environment, enterprise strengthening, small and medium-sized enterprises (SME